La madurez social y su influencia en la inserción laboral de los trabajadores con síndrome de down de la sección laboral de la fundación el Triángulo de la ciudad de Quito, durante el periódo lectivo 2014 – 2015, lineamientos propositivos - Vásconez Campos, Miguel Eduardo (2015)
This research work is about “LA MADUREZ SOCIAL Y SU INFLUENCIA EN LA INSERCIÓN LABORAL DE LOS TRABAJADORES CON SÍNDROME DE DOWN DE LA SECCIÓN LABORAL DE LA FUNDACIÓN EL TRIÁNGULO DE LA CIUDAD DE QUITO, DURANTE EL PERIÓDO LECTIVO 2014 – 2015, LINEAMIENTOS PROPOSITIVOS.” This research was developed in Fundación El Triángulo is located in the city of Quito, Ponciano Bajo, streets Diego Vasquez, dead end street number C, place 21, in order to determine the following problem: How to influence of Social Maturity on the employability of workers with Down Syndrome labor section of Fundación El Triángulo of Quito City during the school year 2014 – 2015?, for this sample was 18 young people from the Fundación El Triángulo, in job placement process. The overall objective of the problem is derived to determine the influence that the degree of social maturity of young people with Down syndrome have on your employment. The methods provided in the research planning process used were: scientific, inductive, descriptive, analytical and statistical model. The techniques used to develop the research were the interview with a representative of Fundación El Triángulo and test of Social Maturity participating youth workers applied, our research had a qualitative approach describing the characteristics of the population to interpret the data obtained by the instruments used. After analyzing the test data and taking as example the question Nro. 2 Expresses feelings through verbal and nonverbal communication, positive or negative emotions expressed in relation to persons or objects. Analyzed the data concluded that: the total of young workers are able to express feelings using verbal and nonverbal communication, or symbolic and they are able to express themselves positively or negatively to a situation or object, with this the first objective was checked: Identify what social characteristics of workers with Down Syndrome labor section of Fundación El Triángulo, to facilitate their employment. To determine benefits for those involved in the process of labor insertion, which is the second objective of our research took the question Nro.10 What are the benefits for those involved in the process of Job Placement? The answer was: the student workers improve their quality of life, co-workers with the presence of young people with disabilities productivity collective challenges imposed because of the great responsibility and perseverance they manifest and the company improves corporate reputation regarding the Fundación El Triángulo profit is the success of its student workers, and become a reference in Job Placement